O assentamento funcional digital: elaboração de um instrumento de padronização de procedimentos para a Pró-Reitoria de Gestão de Pessoas da UFSM - Bortoluzzi, Rosana (2020)
This research contributes in order that the documentary records of the functional trajectory of each federal public worker are accessible in a standardized way to users of the Digital Functional Settlement (AFD) and preserved as a source for research, for guaranteeing rights and as part of institutional memory through work relationships. It also contributes to enrich the literature, by serving as a basis for other studies on AFD. The research aimed to create an instrument for the standardization of procedures for the execution of digitization and registration of documents of the management processes that compose the AFD for the Unified Legal Regime (RJU) within the scope of the Dean of Graduate of People Management (PROGEP) of the Federal University de Santa Maria (UFSM), delimiting to the files from the physical functional folders and contained in version 14 of the Table of Functional Documents (TDF). Concerning the methodology, it is an applied research with a qualitative approach and as the technical procedures it is a case study. Data collection occurred through direct observation, documentary and bibliographic research, as well as interviews with PROGEP/ UFSM workers. The results of the trajectory records of the implementation of AFD at the Institution show that UFSM has been engaged with AFD since its creation in 2011 and since then it has been working to comply with regulations and qualify services towards AFD. Furthermore, we have noticed the relevance of observing the recommendations of the National Archives and the Ministry of Economy (ME) in the digitization and operationalization of the equipment, as well as the definition of the step for digital capture in order to contextualize the AFD in the documents flow. The need to standardize metadata records for inclusion of documents in the system was verified as a way to improve document management and facilitate the work of people management. As a final product, the AFD Manual for PROGEP/UFSM management processes was created, which, after being validated through SCALE Model (Support, Credibility, Accuracy, Legitimacy, Structure), demonstrated to guide PROGEP servers in the execution of digitization activities, metadata registration and inclusion of documents in SIGEPE-AFD in a standardized manner and in line with the ME norms and archival legislation, thus achieving the research objectives. We conclude that technology is constantly revolutionizing the way of transmitting information and documents, and AFD is inserted in this context as a tool that facilitates people management in Brazil through agility in accessing documents, justifying the need for standardization procedures towards it.